2009
DOI: 10.1002/elps.200800501
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis for process development and control of therapeutic protein separation from human plasma

Abstract: The use of proteomics technology during the development of a new process for plasma protein separation was demonstrated. In a two-step process, the two most abundant proteins, human serum albumin and IgG, were removed in a first step of anion-exchange chromatography using a gel with very high capacity. Subsequently, two fractions containing medium and low abundance proteins were re-chromatographed on a smaller column with the same type of gel. Collected fractions were separated by SDS-PAGE and 2D electrophores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Protein bands visible by Coomassie staining that were unique to LANA-1 and ANG lanes (Fig. 1E, lanes 2 and 3) were excised for proteomic analysis using LC-ESI-MS methods at the Midwest Proteome Center, RFUMS (116). Repetition of MS analysis four times demonstrated that only about 30% of the proteins were consistently immunoprecipitated, which corroborated earlier reports (5).…”
Section: Resultssupporting
confidence: 88%
“…Protein bands visible by Coomassie staining that were unique to LANA-1 and ANG lanes (Fig. 1E, lanes 2 and 3) were excised for proteomic analysis using LC-ESI-MS methods at the Midwest Proteome Center, RFUMS (116). Repetition of MS analysis four times demonstrated that only about 30% of the proteins were consistently immunoprecipitated, which corroborated earlier reports (5).…”
Section: Resultssupporting
confidence: 88%
“…Serum itself may be dried and subsequently completely re-dissolved in water; however, treatment with organic solvents and heating can affect the subsequent solubility of blood polypeptides. MS analysis might be used to monitor sample handling and quality procedures (Zheng et al, 2006c;Yi, Kim, & Gelfand, 2007;Gast et al, 2009a;Sun et al, 2009a;Yang et al, 2009a). It may also be possible to store blood samples dried on filter paper (Kulik et al, 2008) or PVDF (Gharahdaghi et al, 1996).…”
Section: Sample Handlingmentioning
confidence: 99%
“…We recently analyzed a highly enriched laboratory IgG concentrate (prepared by cation-exchange chromatography) by use of electrophoretic methods followed by LC-MS/MS, and transferrin, hemopectin, and a-2-macroglobulin were identified as impurities. However, no traces of potentially harmful components were detected [64]. Further detection and characterization of trace proteins can be achieved by use of the above-mentioned techniques for high-throughput analysis [33] and hexapeptide library beads [54], combined with LC-MS/MS.…”
Section: Intravenous Igg Concentratesmentioning
confidence: 99%